2017
DOI: 10.1016/j.neuroimage.2017.02.061
|View full text |Cite
|
Sign up to set email alerts
|

Electrocorticographic delineation of human auditory cortical fields based on effects of propofol anesthesia

Abstract: The functional organization of human auditory cortex remains incompletely characterized. While the posteromedial two thirds of Heschl’s gyrus (HG) is generally considered to be part of core auditory cortex, additional subdivisions of HG remain speculative. To further delineate the hierarchical organization of human auditory cortex, we investigated regional heterogeneity in the modulation of auditory cortical responses under varying depths of anesthesia induced by propofol. Non-invasive studies have shown that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 143 publications
(213 reference statements)
5
14
0
Order By: Relevance
“…In contrast to the "thalamic gating" hypothesis whereby the relay to primary sensory regions is disrupted (38), our results support the notion of preserved PAC responses under light anesthesia (29,33,45), as was also found for LFP responses to visual stimulation (21). Two recent studies examining the effects of propofol on human LFP auditory responses reported preserved early evoked potentials in the most posteromedial part of Heschl's gyrus when compared to intermediate and anterolateral regions showing robust attenuation (46), as well as preservation of novelty responses over short (local deviant) time scales in auditory cortex (47). Our study extends these observations along several dimensions, most importantly by recording spike responses to complex word stimuli.…”
Section: Discussionsupporting
confidence: 87%
“…In contrast to the "thalamic gating" hypothesis whereby the relay to primary sensory regions is disrupted (38), our results support the notion of preserved PAC responses under light anesthesia (29,33,45), as was also found for LFP responses to visual stimulation (21). Two recent studies examining the effects of propofol on human LFP auditory responses reported preserved early evoked potentials in the most posteromedial part of Heschl's gyrus when compared to intermediate and anterolateral regions showing robust attenuation (46), as well as preservation of novelty responses over short (local deviant) time scales in auditory cortex (47). Our study extends these observations along several dimensions, most importantly by recording spike responses to complex word stimuli.…”
Section: Discussionsupporting
confidence: 87%
“…exhibiting a state dependence with useful diagnostic implications. 36 The bursts we observed here are similar to brief UP states or network events observed in vivo under non-rapid eye movement sleep and anaesthesia, 37 38 and are thought to represent fragments of the desynchronized state associated with active engagement with the environment. 14 39 The observation that this type of bistable network activity exists under waking conditions as well 38 40-42 lends further motivation to study this activity in slices.…”
Section: Spiking Responses To Tc and Layer 1 Afferent Stimulationsupporting
confidence: 54%
“…In light of the recent findings of potential contributions from phase-locked activities of the primary auditory cortex to FFRs (Coffey et al, 2016(Coffey et al, , 2017Bidelman 2018), one may also consider the possibility of attention-related cortical mechanisms known to inhibit phase-locking at the auditory cortex to be a factor in modulating the contextdependent FFRs. 1 Recent electrocorticography evidence has suggested that phase-locked neural responses at human posteromedial Heschl's gyrus (HG) is more robust during anesthesia (Nourski et al, 2017). The interpretation to this result was that without anesthesia, simultaneous nonphase-locked synaptic events initiated from other cortical regions may project to posteromedial HG to inhibit phaselocking synaptic events therein.…”
Section: Context-dependent Sensory Encoding Of Speech Signalsmentioning
confidence: 99%
“…The predictive tuning mechanism is likely to be in a constant push-pull with other neural mechanisms such as SSA local to the IC (Lau et al, 2017) as well as cortical inhibition at the HG (Nourski et al, 2017) in mediating sensory encoding in different auditory contexts, as indexed by the FFR. Indeed, a recent FFR study found that the predictability enhancement could be reversed when FFRs were elicited in an irrelevant visual task with high processing load (Xie et al, 2018).…”
Section: Context-dependent Sensory Encoding Of Speech Signalsmentioning
confidence: 99%